Fragmented Narratives in Narayan Wagle’s Palpasa Café: A Postmodern Condition - Paudyal, Ganga Ram (Kaumodaki: Journal of Multidisciplinary Studies, 2026)
This paper examines Narayan Wagle’s novel Palpasa Café from a postmodern perspective, highlighting its multifictional elements, fragmented narratives, and the coexistence of conflicting ideologies and identities. The novel portrays tensions between traditional and modern worldviews, diverse social identities, varying living standards, and differing beliefs regarding the nature and forms of governance. The primary objective of this study is to explore how the novel promotes hyperreality and fragmentation to construct meaning and truth through diverse human experiences. Issues related to postmodernism are analyzed through the theoretical insights of Jean-François Lyotard’s concept of anti-metanarratives and Jean Baudrillard’s notion of simulacra. Adopting a qualitative research approach, this paper reviews relevant critical commentaries and scholarly works on Narayan Wagle and Palpasa Café. The novel, used as the primary source, provides textual evidence of postmodern features by presenting multiple viewpoints through its characters' actions and interactions. By examining the text through the lens of the postmodern condition, the study demonstrates how characters prioritize individual choices and personal concerns over collective ideologies. Since postmodernism emphasizes fragmentation and rejects unified or totalizing narratives, the findings of this study offer insight into the fragmented nature of contemporary society, where meaning is not fixed but generated through multiple and often competing perspectives.